Lesion Topography Impact on Shoulder Abduction and Finger Extension Following Left and Right Hemispheric Stroke - Frenkel-Toledo, Silvi; Ofir-Geva, Shay; Soroker, Nachum (Frontiers in Human Neuroscience, 2020)
The existence of shoulder abduction (SA) and finger extension (FE) movement capacity shortly after stroke onset is an important prognostic factor, indicating favorable functional outcome for the hemiparetic upper limb. Here we asked whether variation in lesion topography affects these two movements in a similar or a distinct way, and whether lesion impact is similar or distinct for left and right hemisphere damage. SA and FE movements were examined in 77 chronic post-stroke patients using relevant items of the Fugl-Meyer test. Lesion effects were analyzed separately for left and right hemispheric damage (LHD, RHD) patient groups using voxel-based lesion-symptom mapping. In the LHD group, SA and FE were affected only by damage to the cortico-spinal tract in its passage through the corona radiata. In contrast, following RHD, these two movements were affected not only by cortico-spinal tract damage but also by damage to white matter association tracts, the putamen and the insular cortex. In both groups, voxel clusters have been found where damage affected SA and also FE, along with voxels where damage affected only one of the two movements. The capacity to execute SA and FE movements following stroke is affected significantly by damage to shared and distinct voxels in the cortico-spinal tract in LHD patients and by damage to shared and distinct voxels in a larger array of cortical and subcortical regions in RHD patients.